PROKRASTINASI AKADEMIK SISWA SMA MARIE JOSEPH KELAPA GADING - Lois Sanggasurya; Henny Christine Mamahit (Universitas Katolik Indonesia Atma Jaya, 2021)
Academic procrastination is the behavior of delaying in doing academic tasks. The behavior of delaying academic assignments by students is related to delays in starting or completing assignments, delays in collecting assignments, time gaps between plans and actions, and doing activities that are more fun than doing assignments. The purpose of this study was to find out in depth the behavior of academic procrastination carried out by a high school student of Saint Marie Joseph Kelapa Gading. This research is a qualitative research with the type of case study research. Data collection techniques were carried out through interviews, observations and filling sheets. The subject of this research is MC. The research showed that the procrastinating behavioral characteristic of MC is the delay in starting or completing the task at hand.